Formation of Common Electricity and Gas Markets in the EAEU: Market Models, Barriers and Solutions - A. A. Migranyan (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2019)
The formation of common industrial markets of the Eurasian Economic Union (EAEU) in the energy sector is not just a task to fulfill the terms of the Treaty on the EAEU, but a necessary condition for expanding integration interaction between partner countries, a necessary resource platform for developing competitive potential in the industrial sector of the EAEU member countries and a factor for ensuring energy security The formation of common industrial markets of the Eurasian Economic Union (EAEU) in the energy sector is not just a task to fulfill the terms of the Treaty on the EAEU, but a necessary condition for expanding integration interaction between partner countries. It’s a necessary resource platform for developing competitive potential in the industrial sector of the EAEU member countries and a factor for ensuring energy security The authors examine in the article the world experience in applying various models for integrating energy markets, in particular electricity and gas, taking into account the specifics of the functioning of the sectoral national systems of the EAEU countries, their resource potential, the level of development of competition and monopolization, and the possibilities of transit of electricity and gas. The potential of creating and developing a common electricity market on the basis of the signed agreements in the EAEU was studied in the context of differences in the institutional and legal bases, the degree of development of competition in the national industrial electricity markets, and their liberalization levels. The revealed differences in the models of the national electricity markets of the EAEU countries cause a long transition period for the formation of a common market with a gradual decrease in the number of seizures in generation / production, transmission and ensuring the security of energy supply to countries. It is noted, that the coordinated model of the transition period does not contribute to the rapid obtaining of significant synergistic effects and the solution of energy redundancy problems. The need to develop a coordinated industrial policy of the EAEU countries to expand the use of resource potential and export of energy resources to third countries is noted. It requires an integrated approach to creating common markets, primarily electricity and gas. (можно дать одним предложением The need to develop a coordinated industrial policy of the EAEU countries to expand the use of resource potential and export of energy resources to third countries is noted, which requires an integrated approach to creating common markets, primarily electricity and gas., а можно оставить и так)The current level of the institutional and legal basis for the formation of the gas market does not allow to overcome the differences in the degree of liberalization of national gas markets, their monopolization and, accordingly, pricing, and determines the acceleration of integration rapprochement. The formation of common markets actualizes the format of exchange trading, the institutionalization of which on the electricity market is already provided for in the EAEU interstate agreements, and on the common gas market requires coordination and implementation of electronic trading mechanisms, drawing on Russian experience.